Use of the Cooperative Script Method in Improving Indonesian Language Learning Outcomes for Elementary School Students - Kamasiah (AIQU: Journal Multidiscipliner of Science, 2023)
The aim of this research is "to improve student learning outcomes in Indonesian language subjects using the Cooperative Script method in Class V of State Elementary School 1 Kaobula". This research is a type of classroom action research which consists of two cycles, where each cycle consists of two meetings. The type of data in this research is quantitative data obtained through learning results tests and qualitative data obtained through observation sheets. Based on the results of data analysis, it was concluded that the application of the cooperative script method could improve student learning outcomes in fairy tale material for Class V students at State Elementary School 1 Kaobula. Pre-cycle the average value of learning outcomes is 54.76 and completeness of learning is 23.80%, cycle I the average value of learning outcomes is 65.47 and completeness of learning is 47.61% and cycle II the average value of learning outcomes is 77.38 and learning completeness 85.71%.